Arroio Chasqueiro Hydrographic Basin (RS): Morphohydrographic Changes Caused by Land Use and Land Cover Dynamics - Simon, Adriano Luís Heck; Felipim, Tamara; Lopes, Ândrea Lenise de Oliveira (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2017)
The anthropic action in hydrographic basins is responsible for the imposition of mechanisms of direct and indirect control about the morphohydrography. The Arroio Chasqueiro Basin, located in the town of Arroio Grande, State of Rio Grande do Sul (Brazil), had its drainage network intercepted after the construction of a reservoir for water collection and the provision of irrigated rice plantations. Coupled with the reservoir construction, there was a spatial reconfiguration linked to the land cover and land use dynamics. This work was carried out with the purpose of identifying and analyzing the morphohydrographic changes in the middle and high basin of the Arroio Chasqueiro (Rio Grande do Sul, Brazil), resulting from the dam imposed to the river system and the land cover and land use dynamics. Detailed geomorphological maps and land use/cover maps between 1947 and 2010 were elaborated, in order to enable the analysis of the occurring changes. The results pointed out for the decrease of rural coverings found in the studied area, with a significant increase of temporary cultures, causing modifications in the spatial configuration of the drainage network and in the landscape forms, with interference on the linked processes. A decrease in the levels of drainage and river densities was noticed highlighting the relations of these changes with the direct and indirect modifications imposed by the land cover and land use dynamics to the morphohydrographic system.